THE ELECTRON MICROSCOPY OF THE HUMAN HAIR FOLLICLE : PART 3. THE INNER ROOT SHEATH AND TRICHOHYALINE - Birbeck, M. S. C. (The Rockefeller University Press, 1957)
1. The three cylinders of cells, each one cell thick, which together constitute the inner root sheath, arise from the peripheral portions of the undifferentiated matrix. These cells, like the hair cuticle, are stabilised by the spread of adhesive contacts between their plasma membranes which occurs in the mid-bulb and upper bulb of the hair follicle. 2. The characteristic intracellular product of all three cell layers is trichohyaline. This substance is formed in the first place as amorphous droplets which subsequently transform into a birefringent form. 3. This transformation, involving the formation of a birefringent product from an amorphous precursor, is in contrast to the formation in the cortex of keratin which originates in a fibrous form. 4. Trichohyaline appears first and transforms first in the cells of Henle which are nearest the outer sheath and the dermal supply vessels. This transformation occurs at the level of the neck of the follicle. Synthesis and transformation in the cells of Huxley and the sheath cuticle lag behind the similar events in the cells of Henle. The transformation does not begin until the lower prekeratinous zone in the Huxley and cuticle cells. 5. The amorpous-fibrous transformation occurs rapidly cell by cell and involves the conversion of all the trichohyaline droplets. In longitudinal sections the birefringent modification can be seen extending from the droplets in both directions parallel to the axis of the hair. In cross-sections the images of the transformed material are difficult to interpret. They may be seen as sections of corrugated sheets (∼100 A thick) or condensed fibrils ∼100 A in width. 6. At the same time that the trichohyaline transforms, the spacing between the cell membranes increases and a dark deposit appears centrally between them. This membrane complex, and the similar complex of the hair cuticle cells described in Part 2, may be specialised formations whose purpose is to hold the hardened cells together.